Host-derived adiponectin is tumor-suppressive and a novel therapeutic target for multiple myeloma and the associated bone disease. - Fowler, J; Lwin, S; Drake, M; Edwards, J; Kyle, R; Mundy, G; Edwards, C (2011)
The contributions of the host microenvironment to the pathogenesis of multiple myeloma, including progression from the non-malignant disorder monoclonal gammopathy of undetermined significance, are poorly understood. In the present study, microarray analysis of a murine model requiring a unique host microenvironment for myeloma development identified decreased host-derived adiponectin compared with normal mice. In support, clinical analysis revealed decreased serum adiponectin concentrations in monoclonal gammopathy of undetermined significance patients who subsequently progressed to myeloma. We investigated the role of adiponectin in myeloma pathogenesis and as a treatment approach, using both mice deficient in adiponectin and pharmacologic enhancement of circulating adiponectin. Increased tumor burden and bone disease were observed in myeloma-bearing adiponectin-deficient mice, and adiponectin was found to induce myeloma cell apoptosis. The apolipoprotein peptide mimetic L-4F was used for pharmacologic enhancement of adiponectin. L-4F reduced tumor burden, increased survival of myeloma-bearing mice, and prevented myeloma bone disease. Collectively, our studies have identified a novel mechanism whereby decreased host-derived adiponectin promotes myeloma tumor growth and osteolysis. Furthermore, we have established the potential therapeutic benefit of increasing adiponectin for the treatment of myeloma and the associated bone disease.